Child and Adolescent Social Adaptive Functioning Scale: Factorial Invariance, Latent Mean Differences, and Its Impact on School Refusal Behavior in Spanish Children - Gonzálvez, Carolina; Inglés, Cándido J.; Martínez-Palau, Ainhoa; Sanmartín, Ricardo; Vicent, María; García-Fernández, José M. (Frontiers in Psychology, 2019)
The aim of this study was to analyze the factorial invariance and latent mean differences across gender of the Spanish version of the Child and Adolescent Social Adaptive Functioning Scale (study 1) and to determine the role of social functioning as a protective factor of school refusal behavior (study 2). The participants were Spanish students aged 8-12 years selected by random cluster sampling, 345 for the first study (M = 9.17; SD = 1.03) and 1,032 students for the second study (M = 10.02; SD = 1.77). The measures used were the Child and Adolescent Social Adaptive Functioning Scale (CASAFS) and the School Refusal Assessment Scale-Revised (SRAS-R). The results of the first study supported the model proposed in this study for the CASAFS, with 15 items and a four-factor structure (School Performance, Peer Relationships, Family Relationships and Home Duties/Self-care). This model remained invariant across gender and adequate levels of internal consistency were obtained (.76, .72, .74 and .71). Latent mean differences did not report differences between boys and girls. Regarding the second study, the social functioning acted as a protective factor of school refusal behavior by negatively and significantly predicting high scores in school refusal behavior based on the presence of anxiety symptoms or feelings of negative affect linked to the obligation to attend school. Opposite results were found for those students who justify their refusal to attend school in pursuing tangible reinforcements outside the school setting. These findings provide strong initial support for the reliability and validity of the CASAFS and the role of social functioning as a protective factor of school refusal behavior is discussed.